Steamboats COLUMBIAN (left), CANADIAN (center) and VICTORIAN (right) at an unidentified dock, probably on the Yukon River, ca. 1899. - University of Washington Libraries. Special Collections Division
PH Coll 246.34 [Meed journal: "Stern-wheel river steamers "Victorian", "Canadian" and "Columbian" owned by the Canadian Development Co. a concern promoted by H. Maitland Kersey. . I gave up my connection with the Bennett Lake & Klondike Navigation Co. at Mr. Kersey's request, acted as Dawson freight and passenger agent for his company during the season of navigation in 1899. At the end of that period the receipts there had exceeded one million dollars at taken in gold dust and nuggets. .] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number